Rzecz o nepotyzmie i kumoterstwie - Rosicki, Remigiusz (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2012)
The paper comprises an introduction, four parts, and conclusions. The introduction char- acterizes the fundamental notions discussed in the paper, namely kin selection, nepotism, cronyism and political capitalism. The first part of the paper concerns kin selection and reciprocal altruism, which are deemed to be the fundamental mechanisms of socialization. This part indicates that nepotism has a biological justification (and in R. Dawkins’ interpretation – a genetic justification). The mechanisms of kin selection and reciprocal altruism raise the question of whether nepotism is not a natural phenomenon in humans. If so, this means that the negative assessment of these phenomena of public life goes against natural human inclinations. The second part of the paper refers to the origins of the notion of nepotism and to a particu- lar understanding of the public realm in modern democracies. The development of democracy has been related to the transformation of the mechanisms of governance which consisted in concessions made by the authorities to those demanding changes. Political struggle has been minimized as it was directed at competition among citizens. The struggle for the change of power has been replaced by the struggle for access to positions and goods in the public realm. Axiological justification has been provided by social justice as a claim for equal access to goods by virtue of principles of transparency. The third part of the paper discusses the issue of nepotism and cronyism in public opinion. It refers to the results of public opinion surveys concerning, among other things, favoritism, ways of looking for jobs, unequal opportunities on account of social status, and the social sta- tus of the family. Additionally, selected examples of nepotism and favoritism in political life are presented. The fourth part deals with the issue of political capitalism both in the interpretation of M. Weber and as a phenomenon of the transition of the Polish socio-political system. Political capitalism can be defined in a nutshell as using state structures or political positions for an un- fair distribution of goods and is expressed by muddy links between the representatives of state with the private business sphere.
On nepotism and cronyism
Keywords: nepotyzm; kumoterstwo; kapitalizm polityczny